Measurement of t(t)over-bar production with additional jet activity, including b quark jets, in the dilepton decay channel using pp collisions at root s=8TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
Jet multiplicity distributions in top quark pair (t (t) over bar) events are measured in pp collisions at a centre-of-mass energy of 8 TeV with the CMS detector at the LHC using a data set corresponding to an integrated luminosity of 19.7 fb(-1). The measurement is performed in the dilepton decay channels (e(+)e(-), mu(+)mu(-), and e(+/-)mu(+/-)). The absolute and normalized differential cross sections for t (t) over bar production are measured as a function of the jet multiplicity in the event for different jet transverse momentum thresholds and the kinematic properties of the leading additional jets. The differential t (t) over barb and t (t) over barb (b) over bar cross sections are presented for the first time as a function of the kinematic properties of the leading additional b jets. Furthermore, the fraction of events without additional jets above a threshold is measured as a function of the transverse momenta of the leading additional jets and the scalar sum of the transverse momenta of all additional jets. The data are compared and found to be consistent with predictions from several perturbative quantum chromodynamics event generators and a next-to-leading order calculation.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Measurement of t(t)over-bar production with additional jet activity, including b quark jets, in the dilepton decay channel using pp collisions at root s=8TeV. European Physical Journal C, 76(7), 56. doi:10.1140/epjc/s10052-016-4105-x
Keywords: Cross-Section; Lhc; Physics